2004
DOI: 10.1029/2003gb002144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modeled versus measured MSA:nss SO4= ratios: A global analysis

Abstract: [1] The MSA:nss SO 4 = ratio, which is a measure of the relative marine biogenic contribution to the total atmospheric sulphur burden, has long been measured in various parts of the globe. Transect studies and observations from a network of stations have provided some idea of the spatial and temporal behavior of the ratio in various regions, but gaps in knowledge still exist in other parts of the globe. Here we present results of a global 3-D chemical transport modeling study which complement these measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 119 publications
(188 reference statements)
7
76
0
Order By: Relevance
“…In East Antarctic Plateau (Concordia Station), by using the same approach, Udisti et al (2012) found the value of 2.6 for a multi-year aerosol database. The ratio = 3.0 evaluated in the 2014 GVB data set is very close to that obtained by the AOE-96 box-model (mean nss-SO 4 2-/MSA = 3.1, Karl et al 2007), and slightly higher than those calculated by a chemical transport model (1.5-2.6; Gondwe et al 2006). By using the SO 4 2-/MSA ratio = 3 in biogenic aerosol originated in the Arctic sea areas, the bio-SO 4 2-fraction can be evaluated by multiplying the MSA concentrations, measured in the Ny-Å lesund aerosol samples, by this value.…”
Section: Sulfate Biogenic Contributionmentioning
confidence: 59%
“…In East Antarctic Plateau (Concordia Station), by using the same approach, Udisti et al (2012) found the value of 2.6 for a multi-year aerosol database. The ratio = 3.0 evaluated in the 2014 GVB data set is very close to that obtained by the AOE-96 box-model (mean nss-SO 4 2-/MSA = 3.1, Karl et al 2007), and slightly higher than those calculated by a chemical transport model (1.5-2.6; Gondwe et al 2006). By using the SO 4 2-/MSA ratio = 3 in biogenic aerosol originated in the Arctic sea areas, the bio-SO 4 2-fraction can be evaluated by multiplying the MSA concentrations, measured in the Ny-Å lesund aerosol samples, by this value.…”
Section: Sulfate Biogenic Contributionmentioning
confidence: 59%
“…These values may be overestimated since an influence of the city of La Paz (3600 m a.s.l., located only at 25 km away from the Chacaltaya site) on the sulfate concentration remains here possible. Note also that other continents, such as Australia, certainly contribute to the long-range transport of continental 210 Pb and sulfate towards Antarctica, in particular in the case of East Antarctica (Heimann et al, 1990). For the first time, 10 Be concentrations are documented in the atmosphere of the high East Antarctic plateau (Fig.…”
Section: A Destruction Of Msa Over the Antarctic Plateau Under Mid-sumentioning
confidence: 88%
“…Therefore, this asymptotic value adequately represents the nss-SO 2− 4 / MSA ratio derived exclusively from DMS . The biogenic SO 2− 4 / MSA ratio has been reported to vary considerably in space and time (Gondwe et al, 2004), because the ratio is sensitive to temperature, and to a lesser extent photochemical species or reactions with halogen radicals (Bates et al, 1992). When this method was applied to data for aerosol samples (PM 10 ) collected in 2014 at the Gruvebadet observatory, in a vicinity of our DMS measurement site, the biogenic SO 2− 4 / MSA ratio was estimated to be 3.0 (Fig.…”
Section: Aerosol Particles Formed During Periods Of Arctic Haze (Aprimentioning
confidence: 99%